2018
DOI: 10.1021/acsenergylett.7b01180
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Engineering of Double-Phase Interface in Mo/Mo2C Heteronanosheets for Boosted Hydrogen Evolution Reaction

Abstract: Two-dimensional Mo/Mo 2 C heteronanosheets (Mo/ Mo 2 C-HNS) were successfully prepared via a NaCl template-assisted synthesis route followed by a controllable simultaneous reduction and carbonization of MoO 3 nanosheets for efficient hydrogen evolution reaction (HER) catalysis under both acidic and alkaline conditions. The Mo species in the atomically thin Mo/Mo 2 C-HNS not only guarantees the rapid transport of electrons but also optimizes the electronic configuration of β-Mo 2 C. Besides, the abundant Mo/β-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(78 citation statements)
references
References 65 publications
1
72
0
2
Order By: Relevance
“…(c) Comparison of η 10 of Mo 2 C‐MoO x /CC( 2 ) with Pt/C and recently reported Mo x C electrocatalysts (ref. samples 1: Mo 2 C@NC nanomesh; 2: Mo 2 C/G‐NCS; 3: Mo 2 C/MoN/NG; 4: Mo/β‐Mo 2 C; 5: N‐Mo 2 C NSs; 6: Mo 2 C/CF; 7: N, P‐Mo x C NF; 8: Fe 3 C‐Mo 2 C/NC; 9: Mo 2 C@GC core–shell nanowire; 10: MoC‐Mo 2 C; 11: Co‐Mo 2 C nanowires; 12: Mo 2 C/CLCN; 13: Mo‐Mo 2 C; 14: MoO 2 ‐Mo 2 C/C; 15: α‐MoC 1− x /β‐ Mo 2 C; 16: 3DHP‐Mo 2 C; 17: Mo 2 C@NC@MoS x ;). (d) Estimation of C dl by plotting the current density variation (Δ j =( j a − j c )/2, at 150 mV vs. RHE.…”
Section: Methodsmentioning
confidence: 99%
“…(c) Comparison of η 10 of Mo 2 C‐MoO x /CC( 2 ) with Pt/C and recently reported Mo x C electrocatalysts (ref. samples 1: Mo 2 C@NC nanomesh; 2: Mo 2 C/G‐NCS; 3: Mo 2 C/MoN/NG; 4: Mo/β‐Mo 2 C; 5: N‐Mo 2 C NSs; 6: Mo 2 C/CF; 7: N, P‐Mo x C NF; 8: Fe 3 C‐Mo 2 C/NC; 9: Mo 2 C@GC core–shell nanowire; 10: MoC‐Mo 2 C; 11: Co‐Mo 2 C nanowires; 12: Mo 2 C/CLCN; 13: Mo‐Mo 2 C; 14: MoO 2 ‐Mo 2 C/C; 15: α‐MoC 1− x /β‐ Mo 2 C; 16: 3DHP‐Mo 2 C; 17: Mo 2 C@NC@MoS x ;). (d) Estimation of C dl by plotting the current density variation (Δ j =( j a − j c )/2, at 150 mV vs. RHE.…”
Section: Methodsmentioning
confidence: 99%
“…/MoC nanofibers via pyrolysis of phosphomolybdic acid-doped polyaniline nanofibers 90. Further experimental results indicated electron transfer from Mo to P and N. Specifically, for Mo 2 C, the charge migration can enhance H adsorption onto Mo sites, whilst for MoC, the N and P act as the basic sites to trap positively protons and mediate proton transfer to the adjacent Mo sites to boost the HER process.TMCs/TMXs hybrids, such as Mo/Mo 2 C,93 Co/β-Mo C,247 MoO 2 /-Mo 2 C,22 Mo 2 N/Mo 2 C,91,241,248 Mo 2 C/Mo 3 Co 3 C, 249 MoC/Mo 2 C, 234, 250 and Mo 2 C/CoP 92 all exhibited appealing electrocatalytic activities for alkaline HER. In a recent study, Yan et al applied an in situ catalytic etching method to prepare a Mo 2 N-Mo 2 C heterostructure.…”
mentioning
confidence: 99%
“…The ECSA of PNC‐4 was 39.3 mF cm −2 , which was higher compared to PNC‐0 (7.5 mF cm −2 ), PNC‐1 (23.7 mF cm −2 ), PNC‐2 (31.3 mF cm −2 ) and PNC‐3 (38.4 mF cm −2 ) as shown in Figure b due to the highest pyridinic N amount in PNC‐4 electrocatalyst, which plays the extraordinarily important role for HER activity. In order to study the HER kinetics, Tafel slopes were extracted from the LSV curves and shown in Figure c, in which the Tafel slope of commercial Pt/C was 30.5 mV dec −1 comparable to previous reported value . Without N doping, PNC‐0 exhibited a much higher Tafel slope of 442.3 mV dec −1 due to the absence of active sites for HER.…”
Section: Resultsmentioning
confidence: 99%